2022
DOI: 10.1097/shk.0000000000002028
|View full text |Cite
|
Sign up to set email alerts
|

A Circulation-First Approach for Resuscitation of Trauma Patients With Hemorrhagic Shock

Abstract: The original guidelines of cardiopulmonary resuscitation focused on the establishment of an airway and rescue breathing before restoration of circulation through cardiopulmonary resuscitation. As a result, the airway-breathing-circulation approach became the central guiding principle of resuscitation. Despite new guidelines by the American Heart Association for a circulation-first approach, Advanced Trauma Life Support guidelines continue to advocate for the airway-breathing-circulation sequence. Although defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Delivery of the ARC bundle was also associated with reduced need for prehospital advanced airway management, an intervention known known to increase prehospital time and mortality. 23 Our findings are consistent with the recent combined analysis of the Prehospital Air Medical Plasma (PAMPer) and Study of Tranexamic Acid During Air Medical and Ground Prehospital Transport (STAAMP) trials, which evaluated the use of prehospital blood products and TXA. This study suggested that every 1 minute of delay in the prehospital administration of blood or TXA was associated with a 2% increase in 30-day mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Delivery of the ARC bundle was also associated with reduced need for prehospital advanced airway management, an intervention known known to increase prehospital time and mortality. 23 Our findings are consistent with the recent combined analysis of the Prehospital Air Medical Plasma (PAMPer) and Study of Tranexamic Acid During Air Medical and Ground Prehospital Transport (STAAMP) trials, which evaluated the use of prehospital blood products and TXA. This study suggested that every 1 minute of delay in the prehospital administration of blood or TXA was associated with a 2% increase in 30-day mortality.…”
Section: Discussionsupporting
confidence: 90%
“…The 3-minute additional prehospital time observed in the ARC group also allowed for 2 U of PRBCs, calcium, and TXA to be administered, interventions that were associated with improved mortality. Delivery of the ARC bundle was also associated with reduced need for prehospital advanced airway management, an intervention known known to increase prehospital time and mortality 23 …”
Section: Discussionmentioning
confidence: 99%
“…We believe that by lowering the isoflurane concentration, we essentially lowered the severity of shock and/or increased the effectiveness of any fluid given, increasing model survivability. Clinically, this supports the idea of prioritizing hemodynamics and basic airway management over advanced airway management requiring intubation and sedation (20).…”
Section: Discussionsupporting
confidence: 64%
“…Overall, there is a growing body of evidence and discussion suggesting that a circulation-first approach is justified when caring for trauma patients, particularly those in hemorrhagic shock. 20 , 21 Patients in hemorrhagic shock are particularly prone to the circulatory collapse associated with early intubation and require adequate resuscitation before airway control. Larger prospective clinical studies in both military and civilian populations are essential to definitively establish the preferred method of resuscitation.…”
Section: Literature Review Supporting Prioritizing Circulation In Inj...mentioning
confidence: 99%